2013
DOI: 10.1109/tuffc.2013.2533
|View full text |Cite
|
Sign up to set email alerts
|

20 years of ultrasound contrast agent modeling

Abstract: The merits of ultrasound contrast agents (UCAs) were already known in the 1960s. It was, however, not until the 1990s that UCAs were clinically approved and marketed. In these years, it was realized that the UCAs are not just efficient ultrasound scatterers, but that their main constituent, the coated gas microbubble, acts as a nonlinear resonator and, as such, is capable of generating harmonic energy. Subharmonic, ultraharmonic, and higher harmonic frequencies of the transmitted ultrasound frequency have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 106 publications
0
109
0
Order By: Relevance
“…1 However, thermal damping can be significant for resonant bubbles larger than about 1 lm and is dominant for resonant bubbles larger than $10 lm.…”
Section: B Contributions To Damping Effectsmentioning
confidence: 99%
“…1 However, thermal damping can be significant for resonant bubbles larger than about 1 lm and is dominant for resonant bubbles larger than $10 lm.…”
Section: B Contributions To Damping Effectsmentioning
confidence: 99%
“…The ideas of compression-only and expansion-dominated behaviors of microbubbles are widely supported as being the main reason for subharmonic generation from phospholipid coated microbubbles [24]- [26]. Even though the dynamics of subharmonic oscillations are not completely understood, it has been demonstrated that the subharmonic generation of the microbubbles depends on the excitation pressure, waveform, and frequency.…”
Section: A Maximizing the Subharmonic Generation From Ucasmentioning
confidence: 99%
“…However, phospholipid-encapsulated microbubbles demonstrate large amplitude oscillations at relatively low pressures. 40,41 Recent studies using ultrafast microscopy revealed asymmetric oscillations, compression only behavior, and low subharmonic thresholds, which cannot be explained by assuming constant coating properties for UCA. 40 We have previously observed this discrepancy-the thresholds for subharmonic oscillations predicted by the modified Rayleigh Plesset model were an order of magnitude higher than those observed experimentally.…”
Section: A Modeling the Dynamics Of Ucas: Theory And Implementationmentioning
confidence: 99%
“…42 The change in the effective surface tension during microbubble oscillations causes rapid changes in shell elasticity, which results in a strong nonlinear response at low pressures-a trend that is consistent with experiments. 40 The Marmottant model assumes that the time dependent radial oscillation of a single microbubble is given by…”
Section: A Modeling the Dynamics Of Ucas: Theory And Implementationmentioning
confidence: 99%